HIV Care Engagement Among Trans Women of Color in San Francisco Bay Area Demonstration Projects: Findings from the Brandy Martell Project and TransAccess. - Wilson, E. C.; Turner, C.; Arayasirikul, S.; Woods, T.; Tryon, J.; Franza, K.; Lin, R. (AIDS & Behavior)
In the San Francisco Bay Area (SFBA), trans women of color are disproportionately affected by HIV and have poor HIV care outcomes. The Brandy Martell Project and TransAccess were two demonstration projects aimed at increasing HIV care engagement and retention among trans women of color in the SFBA. Both projects took place in clinics with a long history of providing trans health care and social services. Both also relied on peer navigation to address systems barriers and promote HIV care linkage and engagement. Our analysis was to identify associations between intervention exposure and primary HIV care visits, ART prescription, and retention in HIV care. Using GEE, we estimated the association between intervention exposure measures (receipt of intervention, intervention dose, intervention provider, and peer dose) and any primary HIV care visit or ART prescription over the 12-month period. Overall, the Brandy Martell Project and TransAccess interventions had significantly positive associations with HIV care outcomes measured. Peer navigation also had a significantly positive association with HIV care outcomes. These interventions demonstrate promise for engaging and retaining trans women of color in HIV care, and call for future investment in this highly underserved community.